2023
DOI: 10.1039/d3ee01211e
|View full text |Cite
|
Sign up to set email alerts
|

Negatively charged platinum nanoparticles on dititanium oxide electride for ultra-durable electrocatalytic oxygen reduction

Abstract: Modulating the metal-support interaction (MSI) have been of rational approach to enhance the kinetics of the supported Pt-based nanocatalysts for oxygen reduction reaction (ORR). However, sluggish activity and poor durability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…To verify the role of surface terminals in suppressing polysulfides shuttle, E b and Li 2 S n ( n ≥ 4) binding strength on 1,3-dioxolane/1,2-dimethoxyethane (DOL/DME) electrolyte solvent molecules are compared (Figure S4). The E b of the two solvent molecules to Li 2 S n ( n ≥ 4) are shown in Figure c, with a value of 0.8–1.0 eV, agreeing well with those (0.74–0.98 eV) reported in previous reports. , Experimental reports have confirmed that the electrides can be stabilized in electrolytes . Li 2 S n ( n ≥ 4) on M 2 CCl 2 has a lower E b and is more inclined to react with the solvent molecules in the subsequent reaction, and polysulfides will dissolve in the solution and cannot be used as candidates.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…To verify the role of surface terminals in suppressing polysulfides shuttle, E b and Li 2 S n ( n ≥ 4) binding strength on 1,3-dioxolane/1,2-dimethoxyethane (DOL/DME) electrolyte solvent molecules are compared (Figure S4). The E b of the two solvent molecules to Li 2 S n ( n ≥ 4) are shown in Figure c, with a value of 0.8–1.0 eV, agreeing well with those (0.74–0.98 eV) reported in previous reports. , Experimental reports have confirmed that the electrides can be stabilized in electrolytes . Li 2 S n ( n ≥ 4) on M 2 CCl 2 has a lower E b and is more inclined to react with the solvent molecules in the subsequent reaction, and polysulfides will dissolve in the solution and cannot be used as candidates.…”
supporting
confidence: 89%
“…17,31 Experimental reports have confirmed that the electrides can be stabilized in electrolytes. 32 Li 2 S n (n ≥ 4) on M 2 CCl 2 has a lower E b and is more inclined to react with the solvent molecules in the subsequent reaction, Exploring van der Waals (vdW) interactions during the adsorption behavior can well describe the adsorption strength of AEs in 2D electrides with polysulfides. We then calculate the ratios of vdW interactions to characterize the effect of vdW forces.…”
mentioning
confidence: 99%
“…The stable oxidation state of Pt atoms in the Pt/SWCNT sustained its high performance and longer durability. These findings align with a prior study that demonstrated how negatively charged Pt nanoparticles, supported by the chemically stable dititanium oxide electride, boost the catalytic activity and sustain performance . Notably, this support structure effectively prevents the formation of a Pt–O skin on the surface of the reduced charged Pt nanoparticles.…”
Section: Resultsmentioning
confidence: 99%